LncRNA AWPPH promotes the proliferation, migration and invasion of ovarian carcinoma cells via activation of the Wnt/β-catenin signaling pathway - Yu, Guangyu (Mol Med Rep, 2019)
The oncogenic role of the long noncoding RNA associated with poor prognosis of hepatocellular carcinoma (lncRNA AWPPH) was reported in various types of malignancies; however, its involvement in ovarian carcinoma (OC) remains unknown. Thus, the present study investigated the role of AWPPH in OC. The expression of AWPPH in tissues and serum acquired from patients with OC, and healthy controls, was determined via reverse transcription-quantitative polymerase chain reaction. The diagnostic value of serum AWPPH expression was evaluated by receiver operating characteristic curve analysis. Additionally, survival curve analysis was performed to determine the prognostic value of AWPPH for OC. An AWPPH overexpression vector was transfected into OC cell lines. Cell proliferation, migration and invasion were analyzed via Cell Counting Kit-8, Transwell migration and invasion assays, respectively. The expression of β-catenin was investigated via western blotting. It was revealed that the expression levels of AWPPH were significantly upregulated in OC tissues and serum compared with healthy controls. The serum levels of AWPPH were able to effectively diagnose and predict the prognosis of patients with OC. AWPPH overexpression promoted the proliferation, migration and invasion of OC cells, and upregulated β-catenin expression. Treatment with a Wnt agonist markedly altered AWPPH expression; however, inhibition of Wnt suppressed the effects of AWPPH overexpression on proliferation, migration and invasion of OC cells. Therefore, it was revealed that AWPPH may promote OC via activation of the Wnt/β-catenin signaling pathway.